Remote Ultrasound Scan Procedures with Medical Robots: Towards New Perspectives between Medicine and Engineering - Maide Bucolo; Gea Bucolo; Arturo Buscarino; Agata Fiumara; Luigi Fortuna; Salvina Gagliano (Applied Bionics and Biomechanics)
Background. This review explores state-of-the-art teleoperated robots for medical ultrasound scan procedures, providing a comprehensive look including the recent trends arising from the COVID-19 pandemic. Methods. Physicians’ experience is included to indicate the importance of their role in the design of improved medical robots. From this perspective, novel classes of equipment for remote diagnostics based on medical robotics are discussed in terms of innovative engineering technologies. Results. Relevant literature is reviewed under the system engineering point of view, organizing the discussion on the basis of the main technological focus of each contribution. Conclusions. This contribution is aimed at stimulating new research to obtain faster results on teleoperated robotics for ultrasound diagnostics in response to the high demand raised by the ongoing pandemic.